Patent Review on Network-based Elderly Healthcare System in the US - Jiang, Chuan; H. Huang, Samuel (Recent Patents on Computer Science, 2013)
Spurred by the aging world, various network–based healthcare systems have been developed to provide and facilitate elderly healthcare service. This paper is intended to provide a review on the state of the art for network-based elderly healthcare systems in the US. Initial search resulted in 41 patents and after careful review 9 representative patents are included in the second round review. These 9 patents are categorized based on their characteristics and explicitly introduced in this paper. The current challenging issues are pointed out and the future development trend is identified in this research area.
Keywords: Elderly